2017
DOI: 10.1515/hf-2016-0162
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose fiber based fungal and water resistant insulation materials

Abstract: The development of thermal insulation materials from sustainable, natural fibrous materials is desirable. In the present study, cellulose fiber based insulation foams made of bleached chemi thermo mechanical pulp (CTMP) have been investigated. To improve water resistance, the foams were impregnated with hydrophobic extractives from the outer bark of birch (Betula verrucosa) and dried. The surface morphology of the foams and the distribution of the deposited particles from the extractives were observed by scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
19
1
1
Order By: Relevance
“…A suspension of CTMP (45 g of pulp fibers were suspended in 1 L of water) was mixed with 0.3 g of sodium dodecyl sulfate foaming agent and either 20% of expandable graphite or 25% of a synergetic intumescent fire retardant according to our previous study. It has beenshown that the thermal insulation materials containing 20% expandable graphite or 25% synergetic fire retardant can meet the requirements of fire class E according to the European standard (CEN [3]; ISO [2]), and show an enhanced fire retardancy (Zheng et al [1]). The mixtures were mechanically stirred (3000 rpm, 15 min) in an L&W Pulp Disintegrator (ABB, Zürich, Switzerland) to form foams, and then the foams that were drained by gravity for 30 min, followed by drying (90°C, 8 h) in a TS8000 oven (TERMAKS, Bergen, Norway).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A suspension of CTMP (45 g of pulp fibers were suspended in 1 L of water) was mixed with 0.3 g of sodium dodecyl sulfate foaming agent and either 20% of expandable graphite or 25% of a synergetic intumescent fire retardant according to our previous study. It has beenshown that the thermal insulation materials containing 20% expandable graphite or 25% synergetic fire retardant can meet the requirements of fire class E according to the European standard (CEN [3]; ISO [2]), and show an enhanced fire retardancy (Zheng et al [1]). The mixtures were mechanically stirred (3000 rpm, 15 min) in an L&W Pulp Disintegrator (ABB, Zürich, Switzerland) to form foams, and then the foams that were drained by gravity for 30 min, followed by drying (90°C, 8 h) in a TS8000 oven (TERMAKS, Bergen, Norway).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Cellulose fiber-based thermal insulating materials could be promising alternatives to the petroleum-based materials to meet the increase in demand for eco-friendly and sustainable building materials [1]. To improve the fire safety of cellulose fiber-based thermal insulating materials used in buildings, different types of fire retardants have been used, such as expandable graphite and a synergetic fire retardant that have low toxicity and low smoke production during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-based materials produced from renewable resources have recently been developed based on bioeconomy and low-carbon economy concepts. Renewable raw materials, such as pulp fiber and recycled textile fiber, have been used to produce value-added products, such as environmentally friendly thermal insulating materials (Zheng et al 2017a, Zheng et al 2017b, Lacoste et al 2018. These materials are promising alternatives to traditional oil-based thermal insulating products.…”
Section: Introductionmentioning
confidence: 99%
“…Betulin-a pentacyclic triterpene alcohol of the lupane family-is one of the main components of birch bark [7]. Over the past ten years, interest in this substance has increased dramatically in connection with its unique antiviral, anti-inflammatory, antitumor properties, and its resistance to fungi and bacteria [8][9][10]. For example, the activity of betulin in relation to the Gram-positive bacterium Staphylococcus aureus is described in works [11,12]; protective properties of betulin against bacterial pneumonia and acute lung injury are described.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [8], betulin was proposed as an antifungal agent for protecting cellulose by impregnating it with a 1-3% ethanol solution. Based on the work, it was shown that the results of the proposed method remain effective for several weeks with respect to strain Aspergillus Brasiliensis.…”
Section: Introductionmentioning
confidence: 99%